STUDENTS SELF-EFFICACY IN ENGLISH SPEAKING PERFORMANCE IN HIGHER EDUCATION - Dini Irawati; Sitti Hadijah; Kiki Aprianti (Sekolah Tinggi Pariwisata Mataram, 2023)
Self-efficacy is one of the factors that influence English-speaking performance. Self-efficacy is a form of self-confidence in a student's competence that allows the student to assess the amount of effort and perseverance needed to complete their task. The purpose of this study is to show students' self-efficacy in English-speaking performance. This research used a descriptive-qualitative method. The subject of this research was a fifth-semester student in the English department of UINSI Samarinda. The data were collected using a questionnaire, interviews, and documentation. The data gathering analyzed the interactive model of Miles and Huberman. The data were validated using source and technical triangulation. Based on the results, researchers found that the self-efficacy of students in speaking English in the fifth semester of the English Education Department at UINSI Samarinda, both in each dimension and as a whole, showed that the level of self-efficacy was in the moderate category. Researchers also found that the magnitude/level dimension is the most dominant dimension in student self-efficacy.